ANALISIS PENGARUH MANAJEMEN PELAYANAN PASTORAL TERHADAP KEPUASAN UMAT WILAYAH III PAROKI SANTA FAMILIA SIKUMANA KEUSKUPAN AGUNG KUPANG - Jimun, Maria Goreti; Kase, Emanuel Bai Samuel; Adinuhgra, Silvester (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
The focus of this research is to analyze the influence of the management of pastoral service on the satisfaction of the people in region III, Santa Familia Sikumana Parish. This is due to the perception that the management of pastoral service implemented in this parish is less than optimal. The sample in this study amounted to 199 people. Data collection uses a questionnaire and document study, while data analysis uses descriptive analysis and inferential analysis. The result showed that descriptively the achievement of the management of pastoral service indicator was 60.81% and people's satisfaction was 53.44%, meaning that both variables were in the fairly good category. Based on inferential statistical analysis, it is known that there is a positive and significant influence of the management of pastoral service on the satisfaction of the people of Region III Santa Familia Sikumana Parish (count value of 15.387 and sig. 0.000 value <0.05). The suggestions offered are that the parish priest needs to implement a management-based pastoral program, involve relevant parties, consistently disseminate pastoral service programs using relevant media, organize and supervise the performance of the pastoral team and parish staff; regional head needs to develop a pastoral service program in region III that are synergistic with parish programs and mobilize people to be actively involved in the program; people need to be critical-constructive towards the implementation of parish pastoral service management and participate in all existing pastoral programs.